The Students’ Mathematic Problem Solving Profile Reviewed on Gender Differences - Aisyah, Amiratih Siti (Al-Khawarizmi, 2023)
The purpose of this research is to clarify how gender differences affect students’ ability to solve mathematical problems. This research uses a descriptive methodology and is classified as qualitative research. Students in SMA Batik 2 Surakarta’s eleventh grade for the 2020/2021 academic year are the research’s subjects. Retrieval of the challenge is finished by way of snowball sampling technique. The strategies of gathering statistics are executed by using the written check of college students’ problem fixing and interview. The research employed problem understanding, answer planning, troubleshooting as deliberate, and re-examining the solution’s outcome as indicators of problem solving. The consequences of the research display that female students can do all trouble solving tiers of mathematics at the same time as male students only perform a little trouble solving stages of mathematics.